Usefulness of Therapeutic Laser for Pain Management in Orthodontic Treatment - Karen Daniela Villavicencio Córdova; Katherim Anahí Cortez Campaña; Pamela Jeanneth Salinas Villacis (Medisur)
Advances in technology and the application of lasers in some areas of dentistry have increased over time. The low power laser has become an effective method for the relief of discomfort in orthodontic treatments. The objective of this research is to determine the usefulness of the therapeutic laser as a tool in the management of pain in orthodontic treatments. A search for scientific articles that mainly covered this topic was carried out in the databases: Google Scholar, Elsevier and the digital journals, American Journal of Orthodontics and Dentofacial Orthopedics, Tamé, the Angle Orthodontics in the period of January 2018 to March 2022. 1410 articles were found, of which 34 studies were chosen that included the use of laser in orthodontic treatments. Of the total selected, 13 were bibliographic review articles, 20 clinical trials and 1 case report. It was determined that the recommended wavelength for a favorable and relieving result to exist, in the areas of pain where the laser is applied, is 810 nm (nanometers) and that the laser sessions can be applied daily or intermittently. with a maximum irradiation of 10 seconds in each area of pain. A maximum of 20 sessions are indicated for the combination of laser orthodontic treatment.